Alveolar epithelial inter-alpha-trypsin inhibitor heavy chain 4 deficiency associated with senescence-regulated apoptosis by air pollution. (1st June 2021) - Chen, Xiao-Yue; Feng, Po-Hao; Han, Chia-Li; Jheng, Yu-Teng; Wu, Chih-Da; Chou, Hsiu-Chu; Chen, Yi-Ying; Wu, Sheng-Ming; Lee, Kang-Yun; Kuo, Han-Pin; Chung, Kian Fan; Hsiao, Ta-Chih; et al.
Abstract: Inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4) is a type II acute-phase protein; however, the role of pulmonary ITIH4 after exposure to air pollution remains unclear. In this study, we investigated the role of ITIH4 in the lungs in response to air pollution. ITIH4 expression in bronchoalveolar lavage fluid (BAL) of 47 healthy human subjects and of Sprague-Dawley rats whole-body exposed to air pollution was determined, and the underlying antiapoptotic and matrix-stabilizing pathways in alveolar epithelial A549 cells induced by diesel exhaust particles (DEPs) as well as ITIH4-knockdown were investigated. We found that an interquartile range (IQR) increase in PM2.5 was associated with a decrease of 2.673 ng/mL in ITIH4, an increase of 1.104 pg/mL of 8-isoprostane, and an increase of 6.918 pg/mL of interleukin (IL)-6 in human BAL. In rats, increases in 8-isoprostane, IL-6, and p53 and a decrease in sirtuin-1 (Sirt1) in the lungs and decreases in ITIH4 in the BAL, lungs, and serum were observed after PM2.5 and gaseous exposure. ITIH4 levels in lung lysates were correlated with levels in BAL samples ( r = 0.377, p < 0.01), whereas ITIH4 levels in BAL were correlated with IL-6 levels ( r = −0.420, p < 0.01). ITIH4 expression was significantly reduced in alveolar epithelial A549 cells by DEP in a dose-dependent manner. A decrease in Sirt1 and increases in phosphorylated extracellular signal-regulated kinase (p-ERK) and caspase-3 were observed after DEP exposure and ITIH4-knockdown. In conclusion, air pollution decreased ITIH4 expression in the lungs, which was associated with alveolar epithelial cell senescence and apoptosis. ITIH4 could be a vital protein in regulating alveolar cell destruction and its inhibition after exposure to air pollution. Graphical abstract: Image 1 Highlights: PM2.5 was associated with an ITIH4 deficiency in the lungs. Decrease of ITIH4 by PM2.5 presented in alveolar epithelial cells of rats. Loss of ITIH4 activated apoptosis and senescence in alveolar epithelial cells. ITIH4 may be a specific protein in response to PM2.5 in alveolar epithelium. Abstract : Capsule of main finding : The significance and novelty of this study are that ITIH4 regulates alveolar cell destruction by air pollution and thus could be an indicator of lung injury due to air pollution.